Peran Babinsa Dalam Upaya Penanggulangan Bencana Banjir Dan Implikasinya Terhadap Ketahanan Wilayah (Studi Pada Babinsa Kodim 0501/Jakarta Pusat BS) - Zaenal Arifin (Jurnal Ketahanan Nasional, 2022)
ABSTRACT This study aims to (1) analyze the factors that influence the role of Babinsa in flood disaster management efforts at Kodim 0501/Central Jakarta BS and (2) analyze the role of Babinsa in disaster management efforts and their response to regional resilience at Kodim 0501/Central Jakarta BS.This study uses a quantitative and qualitative approach. Quantitative to analyze the factors that influence the role of babinsa and qualitative to analyze the role of babinsa. Data sources are primary and secondary data. Primary data were collected by questionnaires, interviews and observations. Secondary data was collected by literature study, documentation, and internet. The role of babinsa is described as it is without intending to make generally accepted conclusions.Babinsa's role in flood prevention is in line with the TNI's duties related to Military Operations Other than War (OMSP) and in accordance with the Babinsa Task Guidance Manual. Central Jakarta has high regional resilience to flooding according to Babinsa at Kodim 0501/Central Jakarta BS. The factors that influence the role of Babinsa simultaneously or partially in flood prevention at Kodim 0501/Central Jakarta BS are education, rank and the amount of training. Babinsa's role in flood management carried out during pre-disaster, during disaster, and post-disaster has positive implications for regional resilience, especially in Central Jakarta.